2021
DOI: 10.1136/bmjopen-2021-049799
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of antenatal Doppler ultrasound for adverse perinatal outcomes in low-income and middle-income countries: a systematic review

Abstract: ObjectivesThis systematic review examined available literature on the prognostic accuracy of Doppler ultrasound for adverse perinatal outcomes in low/middle-income countries (LMIC).DesignWe searched PubMed, Embase, Cochrane Library and Scopus from inception to April 2020.SettingObservational or interventional studies from LMICs.ParticipantsSingleton pregnancies of any risk profile.InterventionsUmbilical artery (UA), middle cerebral artery (MCA), cerebroplacental ratio (CPR), uterine artery (UtA), fetal descend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…35 Our study affirms that fetal cerebral blood flow redistribution is an indicator for intrauterine fetal compromise in the third trimester, a finding particularly important in LMICs, where rigorous evidence on the role of Doppler ultrasound in preventing stillbirths is acutely lacking even though LMICs bear the highest burden of disease. 9,36 Stillbirth rates in sub-Saharan African settings remain substantially high and interventions to reduce their occurrence need to be prioritised. 37 In the current study, the adverse perinatal outcome rates were higher in SGA neonates than in non-SGA neonates, in keeping with previous studies from HICs.…”
Section: Discussionmentioning
confidence: 99%
“…35 Our study affirms that fetal cerebral blood flow redistribution is an indicator for intrauterine fetal compromise in the third trimester, a finding particularly important in LMICs, where rigorous evidence on the role of Doppler ultrasound in preventing stillbirths is acutely lacking even though LMICs bear the highest burden of disease. 9,36 Stillbirth rates in sub-Saharan African settings remain substantially high and interventions to reduce their occurrence need to be prioritised. 37 In the current study, the adverse perinatal outcome rates were higher in SGA neonates than in non-SGA neonates, in keeping with previous studies from HICs.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal and maternal outcomes were assessed at the time of birth and up to 28 days postnatally. Additional information on the EPID study is published elsewhere [12][13][14] . All women recruited to the main prospective cohort provided informed and written consent, with illiterate participants signing using a thumbprint.…”
Section: Design and Participantsmentioning
confidence: 99%
“…This quality assessment study was designed and reported in accordance with the Guidelines for Reporting Reliability and Agreement Studies (GRRAS) 11 . We report on the ultrasound measurement quality control protocols followed in the Ending Preventable Stillbirths by Improving Diagnosis of Babies at Risk (EPID) project, a prospective cohort study implemented between 2018 and 2020 in a rural obstetric care facility in western Uganda [12][13][14] . The primary aim of the EPID study was to determine the predictive performance of Doppler ultrasound for adverse perinatal outcome in a low-resource setting.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Most of the studies have shown moderate prediction accuracy with an improved performance when UtAD is utilized as part of combined models rather than when used alone [20,34,48 ▪▪ ]. A contemporary systematic review from low-income and middle-income countries, found that the UtAD had a poor predictive value for adverse outcomes in most of the manuscripts they included [49 ▪ ].…”
Section: Other Perinatal Outcomesmentioning
confidence: 99%